Exploring smart cities and market transformations from a service-dominant logic perspective. (November 2019) - Ekman, Peter; Röndell, Jimmie; Yang, Ying
Highlights: Explores the emergence of new actors and their roles in the transformation of smart cities. Presents a Service-Dominant logic perspective which supports a holistic understanding of how smart city transformation is closely related to a smart market transformation. Outlines an empirical study on the effects of increased use of renewable energy, such as photovoltaic (PV) systems and their related services, as they are incorporated into smart cities. The article describes the market mechanisms behind the smart city transformation. The study clarifies how the transformation require a broker function to handle the increased information quality and dynamic distribution of energy production and use. Abstract: This study addresses the emergence of new actors and their roles in the transformation of smart cities. By building on a Service-Dominant logic perspective, the study capture how smart city transformation is closely related to a smart market transformation. While prior conceptualizations of markets have followed a linear supply-demand structure, the new market conceptualization can be described as a service ecosystem. The study empirically follows the increased use of renewable energy, such as photovoltaic (PV) systems and their related services, as they are incorporated into smart cities. The results reveal that the overall interaction level among the involved actors increases as the energy market changes from a linear to a networked logic. This transition impacts the market's information quality and, subsequently, the actors' level of required knowledge. The study shows that even if the prevailing actors become more informed, information needs to be 'translated' into 'knowledge-in-context' to become a valuable resource. Thus, the resulting service ecosystem demands a complementary actor that requires the role of a knowledge broker to function. The paper describes the mechanisms behind this smart city transformation and clarifies the broker functions.